2021
DOI: 10.3389/fphys.2021.664071
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Injuries in Ultra-Endurance Running: A Scoping Review

Abstract: Ultra-endurance running (UER) has seen an important increase in participation over the last few decades. Long hours of UER can lead to excessive stress on the body, resulting in musculoskeletal injuries (MSKI). UER is not a uniform sport and events can differ considerably in distance (over 42.195 km), time (e.g., events over 6 h) and multi-day or multi-stage events on various surfaces (e.g., track, on-road, off-road). The aims of this scoping review were therefore: (1) to examine the current evidence of MSKI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Musculoskeletal injuries are common in UER and may affect bones, joints, cartilage/menisci, muscles, tendons, ligaments, and bursae [ 104 107 ]. Around 90% of injuries in UER are overuse in nature [ 104 , 105 , 108 110 ].…”
Section: Long-term Health Implications: Key Aspects By Organ Systemmentioning
confidence: 99%
“…Musculoskeletal injuries are common in UER and may affect bones, joints, cartilage/menisci, muscles, tendons, ligaments, and bursae [ 104 107 ]. Around 90% of injuries in UER are overuse in nature [ 104 , 105 , 108 110 ].…”
Section: Long-term Health Implications: Key Aspects By Organ Systemmentioning
confidence: 99%
“…Several studies has proved that some biomarkers related to ER, increase their values during the race and even some days after completing the test [30,31]. The main markers related to ER in scientific reports are Lactodeshidrogenasa (LDH) and creatine kinase (CK) among liver alterations and inflammatory biomarkers such as leucocytes and protein c-reactive [32][33][34]. The diagnosis of ER remains unclear though, with many different values existing to match ER criteria [24].…”
Section: Introductionmentioning
confidence: 99%
“…These same studies also suggested that this increase might be caused by a rise in intensity. The review on ultra-endurance runners conducted by Scheer and Krabak [28] also suggested that the body region, diagnosis, and rate of injuries differed between competition and training as well as between different ultra-endurance races. While the back, knee, and bone stress injuries are common during training, in short ultra-trail races (65 km), the incidence is higher and it mainly affects the foot (plantar fasciitis), ankle (ankle sprain), and knee.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that there are differences in risk taking between male and female runners [27], being males more prone to sports accidents. However, not only that but there are also sex differences in the type of predominant injuries in male and female ultra-runners [28].…”
Section: Introductionmentioning
confidence: 99%